Vertebral Growth Around Distal Instrumented Vertebra in Patients With Early-Onset Scoliosis Who Underwent Traditional Dual Growing Rod Treatment. Issue 12 (15th June 2019) - Rong, Tianhua; Shen, Jianxiong; Kwan, Kenny; Zhang, Jianguo; Wang, Yahan; Li, Shugang; Li, Zheng; Chen, Chong; Lin, Youxi; Tan, Haining
Abstract : Study Design: Retrospective radiographic study. Objective: To investigate the growth of the vertebrae around distal instrumented vertebra (DIV) in patients with early-onset scoliosis (EOS) who underwent dual growing rod (DGR) treatment. Summary of Background Data: Previous studies indicated that DGR was likely to preserve or even stimulate the spinal growth. However, report pertaining to the effect of growing rod on the growth of individual vertebral body is rare. Methods: The EOS patients treated with DGR who had at least four lengthenings and 5-year follow-up were enrolled. Spine radiographs at index surgery and final follow-up were reviewed. The height, width, and depth of vertebral body from DIV–2 to DIV+2, and the height of the adjacent intervertebral space (IVS) were measured. The percentage of growth was calculated. Results: Thirty-one patients (mean age, 6.2 ± 2.5 years old) met the inclusion criteria, 74.2% (23/31) of whom were female. The average follow-up was 6.2 years (range, 5.0–10.4 yr). The measured vertebrae were divided into DIV group (n = 65), DIV- group (DIV-1 and DIV-2, n = 60), and DIV+ group (DIV+1 and DIV+2, n = 47). There were 33, 90, and 78 measured IVSs in DIV, DIV–, and DIV+ group, respectively. The total percentage growth of vertebral height was significantly higher in DIV– group than that in DIV and DIV+ groups (56.6 ± 20.3% vs. 45.6 ± 18.0% and 42.7 ± 16.2%, respectively, P ⩽ 0.001). The vertebrae in DIV– group also had the highest annual height growth rate (8.7 ± 2.6% vs. 7.0 ± 2.4% and 6.6 ± 2.0%, respectively, P ⩽ 0.001). A significant decrease of IVS height was observed in DIV– and DIV groups ( P ⩽ 0.001). Conclusion: Traditional DGR with periodical distraction stimulated the longitudinal growth of the two segments immediately above DIV in patients with EOS. DGR technique had a negative effect on the development of intervertebral discs within distracted levels. Level of Evidence: 3 Abstract : This study investigated the three-dimensional growth of the vertebrae around distal instrumented vertebra (DIV) in patients with early-onset scoliosis who underwent dual growing rod (DGR) treatment. The results of radiograph measurement indicated that traditional DGR with periodical distraction stimulated the longitudinal growth of the two segments immediately above DIV.